ANALISIS PENGARUH PERSEPSI DUKUNGAN ORGANISASI SEBAGAI MEDIATOR ANTARA PARTISIPASI KARYAWAN DALAM PENGAMBILAN KEPUTUSAN TERHADAP KEPUASAN KERJA DAN KOMITMEN AFEKTIF KARYAWAN NON MANAJERIAL DI PERUSAHAAN FMCG INDONESIA - Sendy Puspaatmaja; Aryana Satrya (Program Studi Magister Manajemen FE Unsri, 2016)
This study aims to analyze the influence of perceived organizational support as a mediator between employee participation in decision making toward job satisfaction and affective commitment of non managerial employees. The research was conducted on 211 non managerial employees at factories in one of FMCG company in Indonesia, use structural equation modeling (SEM) method. The results show that perceived organizational support has an influence as a mediator between employee participation in decision making toward job satisfaction and affective commitment. This can be interpreted that employee participation in decision making is considered able to increase job satisfaction and affective commitment of employees if the organization provides support to the employees